2009
DOI: 10.1063/1.3091280
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared two-color intersubband transitions in AlN/GaN coupled double quantum wells

Abstract: A study on a four-energy-level system in asymmetric AlN/GaN coupled double quantum wells has been performed by solving Schrödinger and Poisson equations self-consistently. It is found that the transition selection rule is recovered when the first two subband pairs resonate in the four-energy-level system. The anticrossing gap between the second excited state (2odd) and the third excited state (2even) can be up to 135 meV when the Al composition of the central barrier is 0.80. The absorption coefficient of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Ungan et al 37 computed the intersubband optical absorptions and refractive index changes in modulation-doped asymmetric double quantum wells. The nonlinear optical absorption in GaInNAs/GaAs double quantum wells under intense laser field was reported by Ungan et al, 38 whereas Cen et al 39 studied the intersubband transition in AlN/ GaN coupled double quantum wells. Despite the important results of the cited works, a systematic study on the linear and nonlinear optical absorptions in double Al x Ga (1Àx) N/GaN quantum wells is still lacking.…”
Section: Introductionmentioning
confidence: 93%
“…Ungan et al 37 computed the intersubband optical absorptions and refractive index changes in modulation-doped asymmetric double quantum wells. The nonlinear optical absorption in GaInNAs/GaAs double quantum wells under intense laser field was reported by Ungan et al, 38 whereas Cen et al 39 studied the intersubband transition in AlN/ GaN coupled double quantum wells. Despite the important results of the cited works, a systematic study on the linear and nonlinear optical absorptions in double Al x Ga (1Àx) N/GaN quantum wells is still lacking.…”
Section: Introductionmentioning
confidence: 93%
“…Next, we turn to calculate the physical parameters modulated by strain and the BEF. The strain tensor components are given by 13 and where a j is the unstrained lattice constant of the j layer material. c 11, j , c 12, j , c 13, j , and c 33, j are the elastic constants, respectively.…”
Section: Strain Modification On Physical Parametersmentioning
confidence: 99%
“…Recent works have shown that this effect obviously influences the impurity and exciton states in wurtzite GaN/Al x Ga 1− x N heterojunctions and QWs 11, 12. A set of detailed discussions about the influence from strain‐induced piezoelectric and spontaneous polarization on the intersubband transition of electrons in AlN/GaN DQWs was presented by Cen et al 13. Analogous to the electronic confinement effect that occurs in semiconductor quantum wells, the resonant photonic states of photonic DQWs composed of two different photonic crystals were studied by Cox and Singh 14 to show the modulation effect of wells and barriers.…”
Section: Introductionmentioning
confidence: 99%
“…The variation in the structural parameters or the externally applied bias or appropriate combination of both can tune the energy subband positions and consequently the intersubband gap in the well to tailor the effective band gap in nanostructures in contrary to the fixed band gap in bulk counterparts. Researchers have utilized this novel feature to design intraband or intersubband photodetectors using multiple quantum well structures for color spectra detection that overcome the limitation of monochromatic wavelength absorption by traditional bulk interband photodetectors [4][5][6]. In recent days Quantum Well Infrared Photodetectors (QWIPs) are widely used for short, mid, long and very-long wavelength infrared detection, thermal imaging, medical imaging and many other real life applications [7][8][9].…”
Section: Introductionmentioning
confidence: 99%